Memoria V Congreso Nacional en Administración de Oficinas: prácticas sostenibles en la administración de oficinas - Vargas Calvo, Margarita (2015)
The Professional Secretarial School since its inception in 1974 has been characterized by promoting spaces for permanent dialogue and reflection with the community, with students, graduates and professionals in the area of Business Education and Office Administration. These aspects are incorporated into the mission and vision of the School, as it will be called in this report. Based on the interest and the principles that are integrated into the mission that highlights the commitment to "Comprehensively train professionals of excellence in the secretarial and / or office administration area in the fields of administrative, business and educational management, meeting the demands of society to contribute to sustainable development”, the V National Congress on Office Administration included in its content issues alluding to the sustainability of practices carried out in office work. Based on what is indicated, the contents are selected based on the recommendations that the participants make in the forms that are used to evaluate each of the topics that are taught in different academic events. Thus, based on these requirements, the Professional Secretarial School organizes this event every two years, transferring the commitment assumed in its mission as part of its work. The objectives that were established for the development of the V National Congress on Office Administration sought to internalize in the attendees the importance of developing their work according to the recommendations to execute a work that responds to the principles of sustainability of management and care for the environment. environment, in order to contribute, from the perspective of social responsibility in the performance of office work.